RELATIONSHIP BETWEEN BIG FIVE PERSONALITY TRAITS AND ADAPTIVE PERFORMANCE: A CONCEPTUAL PERSPECTIVE IN MALAYSIA HEALTHCARE SECTOR (Journal of Technology and Operations Management, 2017)
The purpose of this paper is to propose a conceptual framework on the personality traits and adaptive performance of nurses working at the public hospitals in Malaysia. Current paper is intended to examine the relationship between personality traits using Big Five personality elements and its impact to adaptive performance. Moreover, five personality traits have been used as independent variables which are â€œopenness to experience, emotional stability, conscientiousness, agreeableness and extraversionâ€. Adaptive performance acts as a dependent variable. The findings of the study are supported by the personality theories which is Affective Event Theory (AET). It is assumed to form significant relationship between the personality traits and adaptive performance. For a practical implication, intense focus should be stressed to the factors that can increase employeesâ€™ performance especially in public sector to assure the employees is performed well and can deliver the best service to customers. Social implication for this study is the application of adaptive performance will drive to harmonious working environment which can influence to healthy social life, and practice fast respond to reduce the patientsâ€™ complaints regarding staff performance in public hospitals.